Effects of Aerobic Training and Curcumin Supplementation on Blood Renalase, Creatinin and BUN Levels and Renal Damage in Male Rat Model of Induced Myocardial Infraction - Shiva Ghadirzad; Roghayeh Pouzesh Jadidi; Jabbar Bashiri; Karim Azali Alamdari (Shahid Beheshti University, 2022)
Background and Purpose: The risk of renal injury rapidly increases following myocardial infraction (MI), however; aerobic training and curcumin supplementation have beneficial effects on both the kidneys and the heart post MI. Moreover, blood renalse level can also provide appreciable information regarding these organs health status. Therefore, the aim of study was to investigate the effects of aerobic training and curcumin supplementation on blood renalase, creatinin and blood ure nitrogen (BUN) levels and renal tubular damage in male rat model of induced myocardial infraction.Material and Methods: 40 male wistar rats were randomized into five groups (n=8) of healthy control, MI control, MI training, MI curcumin and MI concomitant (training+curcumin). MI was induced by isoproterenol injection. The training program (consisted of five sessions of running/week at moderate intensity on a treadmill) was conducted throgh eight weeks and curcumin was administrated by gavage method 15 mg/kg.day. Blood renalse was determined by ELISA method, while creatinine and BUN level by enzymatic method and the tissue damge level was evaluated by histologic analysis. The data was analysed by one-way ANOVA (Tokey test as post hoc) and Chi square tests with a confidence level of 95%.Results: Blood renalse (P = 0.001), creatinine (P = 0.001) and BUN (P = 0.025) was significantly higher in MI control group compared to healthy controls. However, the amounts of these indices had no significant differences with MI control group in all three intervention groups of MI training, MI curcumin and MI concomitant (P > 0.05). However; renal injury was significantly lower in all three intervention groups than MI control group (P = 0.007, P = 0.037 and P = 0.001 respecetively) and also in MI concomitant group compared to both of MI training (P = 0.006) and as well as MI curcumin (P = 0.003) groups.Conclusion: The hazardous effects of MI on all three variables could be ameliorated following all three interventions. However, the concomitant intervention is superior to both of the aerobic training as well as curcumin supplementation for reductions in the histologic injury level.